2016
DOI: 10.18632/oncotarget.9265
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of MCP-1/CCR4 signaling-induced recruitment of activated regulatory cells evokes an antitumor immune response in head and neck squamous cell carcinoma

Abstract: FoxP3+ regulatory T (Treg) cells have diverse functions in the suppression of antitumor immunity. We show that FoxP3hiCD45RA−CD4+ Treg cells [activated Treg (aTreg) cells] are the predominant cell population among tumor-infiltrating FoxP3+ T cells, and that high aTreg cell-infiltrating content is associated with reduced survival in patients with head and neck squamous cell carcinoma (HNSCC). In vitro studies have demonstrated that aTreg cells can suppress tumor-associated antigen (TAA) effector T cell immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
(55 reference statements)
4
31
0
Order By: Relevance
“…Consistently with this hypothesis the increased expression of Monocyte Chemotactic Protein-1 (MCP-1), C-C motif Chemokine Ligand 22 (CCL22), C-C chemokine receptors type 4 and 7 (CCR4 and CCR7), that are associated to a migratory phenotype, has been observed on HNSCC isolated Treg and in HNSCC tissue. 10,11,35,48 In addition, ligands for CCR4 and CCR7 were more expressed in HNSCC if compared with the adjacent healthy tissue. 10 In partial disagreement with the above-reported data, Sun and coworkers found high level of CCR7 C cells in the peripheral blood of HNSCC, but CCR7 expression was elevated in all T lymphocytes, irrespective of the subsets.…”
Section: Mechanism Of Treg Accumulation In Hnsccmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently with this hypothesis the increased expression of Monocyte Chemotactic Protein-1 (MCP-1), C-C motif Chemokine Ligand 22 (CCL22), C-C chemokine receptors type 4 and 7 (CCR4 and CCR7), that are associated to a migratory phenotype, has been observed on HNSCC isolated Treg and in HNSCC tissue. 10,11,35,48 In addition, ligands for CCR4 and CCR7 were more expressed in HNSCC if compared with the adjacent healthy tissue. 10 In partial disagreement with the above-reported data, Sun and coworkers found high level of CCR7 C cells in the peripheral blood of HNSCC, but CCR7 expression was elevated in all T lymphocytes, irrespective of the subsets.…”
Section: Mechanism Of Treg Accumulation In Hnsccmentioning
confidence: 99%
“…10 In partial disagreement with the above-reported data, Sun and coworkers found high level of CCR7 C cells in the peripheral blood of HNSCC, but CCR7 expression was elevated in all T lymphocytes, irrespective of the subsets. 48 Only the increased expression of CCR4 is a peculiar characteristic of Treg isolated from HNSCC patients. CCR4 expression is a marker of Treg activation as CCR4…”
Section: Mechanism Of Treg Accumulation In Hnsccmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumors can escape from their host immune system in various ways, one of which is via regulatory T cells (Tregs) to suppress tumor‐specific T‐cell responses . This study and other studies have shown that host antitumor immune response could be effectively enhanced by depletion or functional inhibition of Tregs …”
Section: Introductionmentioning
confidence: 74%
“…In that study, CCR4 was predominantly expressed by activated regulatory T cells but not significantly expressed by CD8 T cells. Using a migration assay, it was shown that CCR4‐CCL2 signaling was involved in trafficking of activated regulatory T cells .…”
Section: Discussionmentioning
confidence: 99%